Therapeutic Role of Tocilizumab in SARS-CoV-2-Induced Cytokine Storm: Rationale and Current Evidence - Corrado Pelaia (International Journal of Molecular Sciences, 2021)
Among patients suffering from coronavirus disease 2019 (COVID-19) syndrome, one of the worst possible scenarios is represented by the critical lung damage caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2)-induced cytokine storm, responsible for a potentially very dangerous hyperinflammatory condition. Within such a context, interleukin-6 (IL-6) plays a key pathogenic role, thus being a suitable therapeutic target. Indeed, the IL-6-receptor antagonist tocilizumab, already approved for treatment of refractory rheumatoid arthritis, is often used to treat patients with severe COVID-19 symptoms and lung involvement. Therefore, the aim of this review article is to focus on the rationale of tocilizumab utilization in the SARS-CoV-2-triggered cytokine storm, as well as to discuss current evidence and future perspectives, especially with regard to ongoing trials referring to the evaluation of tocilizumab’s therapeutic effects in patients with life-threatening SARS-CoV-2 infection.